The notebook - Cassavetes, Nick.; Gosling, Ryan, 1980-; McAdams, Rachel, 1976-; Garner, James; Rowlands, Gena.; Marsden, James, 1973-; Connolly, Kevin, 1974-; Thornton, David; Brown, Jamie Anne.; Wahlquist, Heather; Shepard, Sam, 1943-; Allen, Joan, 1956-; et al. ([S.l.] : New Line Home Entertainment, 2005)
The movie revolves around Noah Calhoun's regular visits to a female patron of an area nursing home. Rather than bore her with the inanities of everyday life, Calhoun reads from an old, faded notebook containing the sweeping account of a young couple whose love affair was tragically put to a halt after their separation in the midst of World War II. Seven years later, the couple was reunited, and, despite having taken radically different paths, they found themselves unable to resist the call of a second chance.
DVD; Dolby digital surround; Region 1, DVD, widescreen and fullscreen presentations, Region 1, EX 5.1 surround sound, stereo. surround sound.
In English with optional English or Spanish subtitles.
Closed-captioned.
Ryan Gosling, Rachel McAdams, James Garner, Gena Rowlands, James Marsden, Kevin Connolly, David Thornton, Jamie Anne Brown, Heather Wahlquist, Sam Shepard, Joan Allen.
Director of photography, Robert Fraisse ; editor, Alan Heim ; music, Aaron Zigman.
Based on the novel by Nicholas Sparks.
Keywords: First loves -- Drama; Social classes -- Drama; Young adults -- Conduct of life -- Drama; Feature films; Video recordings for the hearing impaired